PEMBELAJARAN MENULIS KARANGAN ARGUMENTASI MENGGUNAKAN METODE GUIDE INQUIRI - Muhammad Hendra; Retno Septianti; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on the low ability of students in writing an essay of argumentation on the high school level. The ability to write is important in education, because by writing students easily pour ideas, feelings, and change the form of sounds that are heard into papers. Learning writing emphasizes students to be able to describe a variety of ideas, ideas, feelings, opinions, or thoughts. This study uses a guided inquiry method. Through the method of guided inquiry students are strived to maximize learning to make an argumentation essay. Before conducting research, researchers prepare to learn plans including the preparation of syllabi and RPP. In the preparation of the RPP, there are several parts, the components that must be fulfilled such as identity, competency standards, basic Competencies, and so on. Significant differences in outcomes from the use of Guide inquiry method between before and after in Harapan Baru high school students in Bekasi. From an average of 67.4 initial tests to 75.7 in the final test.